Nanosecond Pulse Generation with Silver Nanoparticle Saturable Absorber - Rosdin, Raja Zaimas Rosdin Raja; Ahmad, Muhammad Taufiq; Muhammad, Ahmad Razif; Jusoh, Zulzilawati; Arof, Hamzah; Harun, Sulaiman Wadi (IOP Publishing, 2019)
Nanosecond pulse generation in an erbium-doped fiber laser (EDFL) passively mode-locked by a silver nanoparticle (SNP)-based saturable absorber (SA) is experimentally demonstrated. The SA is fabricated by depositing a nanosized SNP layer onto the surface of polyvinyl alcohol film through the thermal evaporation process. By inserting the SA into an EDFL cavity, stable mode-locked operation is achieved at 1561.5nm with the maximum pulse energy up to 52.3 nJ. The laser operates at a pulse repetition frequency of 1.0MHz with a pulse width of 202 ns. These results suggest that SNPs could be developed as an effective SA for mode-locking pulse generation. © 2019 Chinese Physical Society and IOP Publishing Ltd.